(untitled) (ESMAT Magazine, 2025)
This paper addresses legal psychology, a field that combines knowledge of psychology and law to understand human behavior in legal contexts. Legal psychology has become an essential tool in the justice system, helping judges and other professionals make more informed and fair decisions. The objective of this study is to analyze how the work of legal psychologists contributes to the Brazilian judicial system, exploring their different areas of practice and the influence of psychological knowledge on judicial decisions. The methodology used was a qualitative literature review, based on studies and academic publications that discuss the historical development, definitions, and practices of legal psychology. During the research, topics such as the work of psychologists in various areas of law were explored, including family, criminal, civil, labor, and child and adolescent protection law. In addition, the techniques and methods used by these professionals to prepare reports, mediate conflicts, and offer psychological support in legal proceedings were analyzed. In conclusion, it can be said that legal psychology has established itself as an indispensable specialty in the judicial system, promoting ongoing dialogue between psychology and law. The work of these professionals contributes to the fairer and more humane application of justice, valuing the complexity of the behaviors and contexts involved. It is recommended that future studies continue to explore new forms of action and methods that can improve this area, strengthening its relevance and impact on society.